Effects of Aerobic Exercise vs. Resistance Training on Endothelial Function in Women with Type 2 Diabetes Mellitus - Kwon, Hwi Ryun; Min, Kyung Wan; Ahn, Hee Jung; Seok, Hee Geum; Lee, Jae Hyuk; Park, Gang Seo; Han, Kyung Ah (Diabetes & metabolism journal, 2011)
There is controversy over whether aerobic or resistance exercise is more effective for improving endothelial function in type 2 diabetes mellitus (T2DM). This study was aimed to investigate the effects of an aerobic and resistance training program on endothelial function, and the influences of glycemic control, body weight changes, and aerobic capacity in T2DM. Total 40 overweight women with T2DM were assigned into 3 groups: an aerobic exercise group (AEG, n=13), resistance exercise group (REG, n=12), and control group (CG, n=15), and followed either brisk walking for the AEG or resistance band training for the REG, 60 minutes per day, 5 days per week for 12 weeks with monitoring daily activity using accelerometers. We assessed endothelial function by flow-mediated dilation (FMD), and aerobic capacity by oxygen uptake at anaerobic threshold (AT_VO(2)) at baseline and following training program. The mean participants' age was 57.0±6.8 years, and body mass index (BMI) was 27.0±2.3 kg/m(2). After intervention, FMD increased by 2.2±1.9% in AEG, which differed from REG and CG (P=0.002), despite of decreased body weight (BW) in both AG and RG (2.8±2.5%, P=0.002; 1.6±2.0%, P=0.017, respectively). A significant increased AT_VO(2) and decreased HbA1c were found only in AEG. In all participants, FMD was changed with the significant relations to the AT_VO(2) (r=0.348, P=0.035), but not to HbA1c levels or BW. Aerobic exercise appears to be more beneficial than resistance exercise for improving endothelial function in T2DM. In addition, aerobic capacity could be a better predictor of changes in FMD than BW and glycemic control.